Bears and Humans, a Neanderthal tale. Reconstructing uncommon behaviors from zooarchaeological evidence in Southern Europe - Matteo Romandini; Gabriele Terlato; Nicola Nannini; Antonio Tagliacozzo; Stefano Benazzi; Marco Peresani (Journal of Archaeological Science, 2018)
Cave bear (Ursus spelaeus), brown bear (Ursus arctos), and Neanderthals were potential competitors for environmental resources (shelters and food) in Europe. In order to reinforce this view and contribute to the ongoing debate on late Neanderthal behavior, we present evidence from zooarchaeological and taphonomic analyses of bear bone remains discovered at Rio Secco Cave and Fumane Cave in northeast Italy, an extended geographic area north of the Adriatic Sea. The remains from both caves come from layers dated to 49-42 ky cal. BP, and suggest close interactions between humans and bears, with data not only limited to the association of Mousterian lithic artifacts with numerous bear remains, but also the detection of clearly preserved traces of human modification such as cut and percussion marks, which enable a reconstruction of the main steps of fur recovery and the butchering process. Examples of Neanderthal bear exploitation are extremely sporadic in Europe, and Grotta Rio Secco and Grotta Fumane can be considered rare cases of remain accumulations generated by the human predation of bears of varied age classes during or near the end of hibernation. All of this evidence suggests that bears had a strategic role in the nomadic economy of Neanderthal hunting groups.